Acrylamide optical sensor based on hydrolysis using Bacillus sp. strain ZK34 containing amidase properties - Chong, Yee May; Musa Ahmad,; Lee, Yook Heng; Norzila Kusnin,; Mohd Yunus Abdul Shukor, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this work, a new optical screening method for acrylamide was developed. Bacterial Bacillus sp. strain ZK 34 was used to hydrolyse acrylamide to the corresponding acid and ammonia. Nessler’s reagent was used to detect the produced ammonia and the yellow complex formed was treated as signal. Bacterial pellet was immobilised in the alginate membrane. The optimum composition of alginate used is 2%. The mass ratio of alginate:bacterial of 1:0.5 gave the optimum respond. Optimum concentration for NaOH and Nessler’s reagent were 0.075 M and 2.5 mM, respectively. The yellow complex of mercury (II) amido-iodine formed was directly proportional to the concentrations of acrylamide up to 50.00 ppm with the limit of detection of 1.30 ppm. This sensor shows a good reproducibility which the relatives standard deviation (RSD) values from 3.17-6.15%. Therefore, the detection of acrylamide based on the amidase hydrolysis is suitable for screening this carcinogen compound.